Satisfaction Level Spiritual Care of Coronary Heart Disease Patients Using Spiritual Assessment Tool - Wisuda, Aris Citra; Sansuwito, Tukimin bin; Suraya, Citra; Rusmarita (Yayasan Rumah Ilmu Professor, 2023)
with using application of Spiritual Assessment Tool. This type of research is descriptive analytic with cross sectional approach. results In this study, it is known that the age of the respondents is mostly in the age range of (>35 Year old age), which is as much as 81.8%. Most of the patient education is low education which is as much as 72.7%. Patient Satisfaction Spiritual Care in the pre-test is known to be mostly stated as not satisfied, as much as 68.2%, and in the post-test, Patient Satisfaction Spiritual Care experienced a change in that the patient stated that he was satisfied as much as 90.9%. In conclusion, spiritual care can increase patient satisfaction, especially coronary heart disease sufferers at Siti Khadijah Islamic Hospital, Palembang in 2023.